2009
DOI: 10.1123/ssj.26.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Blogging the 2006 FIFA World Cup Finals

Abstract: This study focuses on the use of new technologies by the sports-media complex, looking specifically at the 2006 FIFA World Cup Finals. Combining the world’s single largest sports media event with one of the most current, complex forms of Web-based communication, this article explores extent to which football fans embedded in Germany used the Internet to blog their World Cup experiences. Various categories of blog sites were identified, including independent bloggers, bloggers using football-themed Web sites, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Horne and Whannel (2010, p. 767) believe that the 'power and influence to shape the agenda -and construct the story -remain tied to large media organisations despite the internet and the emergence of heterogeneous voices'. Dart (2009) agrees, arguing that the democratising potential of new media did not transpire during the 2006 FIFA World Cup Finals in Germany, mainly because corporations became advanced in using consumer-generated media to further their commercial imperatives. He argues that the established media essentially appropriated and incorporated fans' desire to feed the sporting event discourse and sought ever more complex ways to monetise these interactions.…”
Section: Leisure Studies 99mentioning
confidence: 85%
“…Horne and Whannel (2010, p. 767) believe that the 'power and influence to shape the agenda -and construct the story -remain tied to large media organisations despite the internet and the emergence of heterogeneous voices'. Dart (2009) agrees, arguing that the democratising potential of new media did not transpire during the 2006 FIFA World Cup Finals in Germany, mainly because corporations became advanced in using consumer-generated media to further their commercial imperatives. He argues that the established media essentially appropriated and incorporated fans' desire to feed the sporting event discourse and sought ever more complex ways to monetise these interactions.…”
Section: Leisure Studies 99mentioning
confidence: 85%
“…they do not seek to engage in a participatory role in football-related consumption and interaction), for Cleland (2010) and Dart (2009), the creation of blogs and message boards has encouraged a number of active football supporters to take up a more participatory role in exchanging information and thoughts. These fans are also found to be some of the most committed as, according to Gibbons and Dixon (2010), they are also regular attenders of matches, which is often seen as a traditional and authentic practice.…”
Section: Football Fan Discourse and The Internetmentioning
confidence: 99%
“…While new media are challenging the popularity and profits of traditional, mainstream media organizations, at issue is the extent to which control is being asserted this "old" media. While audiences search for ways of connecting to global sporting events, which can circumvent existing structures, the above studies echo that found by Dart (2009) illustrates is a shift in attitude and behaviour. Fearful of its potential to destabilize the long-standing, mutually beneficial relationship between the mainstream media, sports governing bodies and sponsors (Jhally's "golden triangle"), they have each sought to reposition themselves.…”
Section: Sports Teams and Organizations And New Media Technologymentioning
confidence: 48%
“…iii So while new media does allow sports fans to bypass the mainstream media and set up their own blog or e-zine, as a former CEO of Google noted "the average blog has one reader: the blogger" (quoted in Leonard, 2006). As Dart (2009) found in his research during the 2008 FIFA World Cup finals, the mainstream media used their cross platforms and partner corporations to successfully colonize and dominate football fans' online activity. One conclusion one might draw is that once the florid rhetoric of self-organization, openness and a bottom-up participatory, democratizing culture is subject to scrutiny, the reality of "new" media is one of an overarching, top-down corporate controlled structure (see also Gallagher & Syal, 2011;Lehmann, 2011).…”
Section: New Media Technology and Sport: Controlling The Contentmentioning
confidence: 99%